Investment Market Tool for Young People - Torres Garcia, Miguel Ernesto (Jihočeská univerzita, 2022)
This thesis presents an investment decision tool, allowing to select the best strategy for maximizing their resources, when young people in the Czech Republic are faced with the dilemma of buying a house or living via rent and making an investment with a possible extra money they have. Nowadays, the housing market might be too expensive for the common people. Based on national average dwelling prices and average income, saving for the down payment might take several years. Also, the mortgage monthly payments can take a sizable part of a person income. The tool is written in Microsoft Excel? using VBA programming language to predict investments portfolios return and compare it to a hypothetical mortgage. Several scenarios can be saved for further analysis and the tool has the possibility to include further investment options and prediction techniques. Several examples are given to show the utility as well as a survey of potential users that have evaluated this tool.
Investment Market Tool for Young People
Keywords: Mortgage; Investment; Excel; Forecast; Mortgage; Investment; Excel; Forecast